UPAYA DINAS PENDIDIKAN KOTA PEKANBARU DALAM MENINGKATKAN NILAI AKREDITASI SEKOLAH DASAR DI KOTA PEKANBARU TAHUN 2012 - Nadya Anggita; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Pekanbaru city government that has the responsibility and authority toimprove the quality of education is Pekanbaru City Department of Educationwhich is part of the local government under Law No. 32 Year 2004 on RegionalGovernment. One way to improve the quality of education is through schoolaccreditation. With the expected quality of education accreditation PekanbaruCity can continue to increase and become a benchmark for the success ofeducational programs that can be an example for other areas in Riau provinceand outside the province of Riau.The purpose of this study is to see how the efforts of Pekanbaru CityDepartment of Education in improving the quality of education throughaccreditation and any factors that hamper the government's efforts in improvingaccreditation. This research was conducted in the city of Pekanbaru, which is thekey informants in this study are, the head Pekanbaru City Department ofEducation, the head of Primary School Development. In collecting the dataobtained from the documentation and documentation - depth interviews withinformants. Once the data is collected and then analyzed using qualitativedescriptive analysis. After doing research, efforts to increase the value ofaccreditation is not yet fully optimized.It was also found that there are factors that hamper efforts PekanbaruCity Department of Education in improving primary school accreditation. Thelimiting factor is the lack of funds for education, lack of teachers and educationpersonnel, lack of infrastructure facilities, and management education has notbeen effective and efficient. Suggestions for official efforts to improve elementaryschool accreditation is a further need to be maximized, socialization shouldperiodically be given to schools to better prepare future components ofaccreditation in order to 8 components in the accreditation assessment can beprepared as much as possible.Key word : elementary school accreditation, the quality of education.